1995
DOI: 10.1016/s0022-5347(01)67315-4
|View full text |Cite
|
Sign up to set email alerts
|

Triple Therapy in Cadaveric Renal Transplantation: Role of Induction Cyclosporine and Targeted Levels to Avoid Rejection

Abstract: The updated data on 61 consecutive cadaveric transplants performed at our institution from 1987 to 1990 (followup 31 to 82 months, median 54 months) were analyzed with emphasis on cyclosporine monitoring and long-term results. All patients received triple therapy with cyclosporine induction, azathioprine and prednisone regardless of graft function, and they were preferentially placed on the calcium blocker nifedipine. We monitored 12-hour cyclosporine trough levels in whole blood using high performance liquid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
2001
2001

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Several studies have demonstrated different therapeutic ranges for cyclosporine in which overexposure or underexposure has been correlated with poor transplant outcomes. [14][15][16][17][18][19] Going outside the therapeutic range for immunosuppressive drugs can lead to serious clinical consequences for the transplant recipient. Underexposure to cyclosporine or tacrolimus may contribute to an increased incidence of acute rejection and subsequent graft loss, whereas overexposure can result in nephrotoxicity, infections, and malignancies.…”
Section: Calcineurin Inhibitors: Critical-dose Drugsmentioning
confidence: 99%
“…Several studies have demonstrated different therapeutic ranges for cyclosporine in which overexposure or underexposure has been correlated with poor transplant outcomes. [14][15][16][17][18][19] Going outside the therapeutic range for immunosuppressive drugs can lead to serious clinical consequences for the transplant recipient. Underexposure to cyclosporine or tacrolimus may contribute to an increased incidence of acute rejection and subsequent graft loss, whereas overexposure can result in nephrotoxicity, infections, and malignancies.…”
Section: Calcineurin Inhibitors: Critical-dose Drugsmentioning
confidence: 99%